I really wonder what plant I'm growing - Child, Lauren (London : Puffin, 2008)
Lola learns all about how to grow a plant from her older brother, Charlie, and wonders what her seeds will produce once they have come to term.
"A storybook puzzle pack."
"As seen on Playhouse Disney."
Cover title.
Includes a jigsaw puzzle.
On board pages.
2.4.
Keywords: Brothers and sisters -- Juvenile fiction; Seeds -- Juvenile fiction; Toy and movable books -- Specimens; Brothers and sisters -- Fiction; Plants -- Fiction; Seeds -- Fiction; Toy and movable books; Plants -- Fiction; Seeds -- Fiction; Siblings -- Fiction; Toy and movable books